Evaluation of the effects of 2D animation on business law: Elements of a valid contract - Rahim, Sarni Suhaila; Parumo, Shahril; Fadlan Faizal, Nur Zulaiha; Parumo, Shahril (The Science And Information (SAI) Organization Limited, 2023)
This article presents an evaluation of Business Law 2D Animation: Elements of a Valid Contract. The developed application was produced to assist business law students to understand the contents of the topic Elements of a Valid Contract. An experiment was carried out to assess the usability of the application as a learning and review material for business law students. This study comprised five major evaluation components, including learnability, usability, accessibility, functionality, and effectiveness, to investigate user involvement and satisfaction with the proposed educational learning system. To acquire user testing results, online questionnaires were issued. There was a total of 63 respondents, including multimedia experts, students, and subject matter experts. The findings of the current study revealed that the majority of respondents were pleased with the outcomes of the animation. The results may assist in improving the teaching of the topic Elements of a Valid Contract for business law students as it provides visually appealing method of learning